Strategi Komunikasi Dakwah Gus Badar Pada Komunitas Jaljalut - Falahuddin Ma'ruf , An'im; Ulfa Ni’amah, Luthfi (Institut Agama Islam Negeri Kerinci, 2023)
This research was described the da’wah communication strategy implemented by Gus Mochammad Badaruddin Abdulloh in da’wah activities of Jaljalut community. This research was used a qualitative approach by observations, interviews, and collecting the evidence by field documentation. The data obtained was analyzed by data reduction, visualization, and conclusion/verification. Based on the results of the research, it was found that the main target in preaching from the Jaljalut community is young people, especially children who live on the streets. The success of Gus Badar’s preaching to the Indonesian Jaljalut community was greatly influenced by the use of the right approach strategy, as well as the selection of media according to their preferences and tendencies towards mad’u. The result of this research was found in three formulations of da’wah strategies, namely sentimental da’wah strategies, rational strategies, sensory strategies that preachers can use in conveying their da’wah. It is hoped that the three da’wah communication strategy formulations found in this study can help preachers convey their da’wah materials to mad’u.